2014
DOI: 10.1186/1471-2466-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life is associated with physical activity and fitness in cystic fibrosis

Abstract: BackgroundHealth-related and disease-specific quality of life (HRQoL) has been increasingly valued as relevant clinical parameter in cystic fibrosis (CF) clinical care and clinical trials. HRQoL measures should assess – among other domains – daily functioning from a patient’s perspective. However, validation studies for the most frequently used HRQoL questionnaire in CF, the Cystic Fibrosis Questionnaire (CFQ), have not included measures of physical activity or fitness. The objective of this study was, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 31 publications
(59 reference statements)
6
96
5
1
Order By: Relevance
“…5 Our findings are in line with this study and extend this association to measures of selfesteem, which is also compromised in CF. 30 These findings underline the importance of a high level of peak aerobic capacity as a contributor to psychological and sociological well-being.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…5 Our findings are in line with this study and extend this association to measures of selfesteem, which is also compromised in CF. 30 These findings underline the importance of a high level of peak aerobic capacity as a contributor to psychological and sociological well-being.…”
Section: Discussionsupporting
confidence: 90%
“…5 Based on significant associations with quadriceps strength, 12,28 the STS test has been proposed as a simple measure of lower-limb strength. We expressed STS repetitions as a product of body weight because this factor clearly influences STS performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the BMI of patients with CF did not differ when they were categorized in different physical activity levels through the IPAQ questionnaire. In contrast with our findings, previous studies have shown that malnourishment in this population is associated with impairment of pulmonary function, loss of musculoskeletal muscles, fatigue, and reduction in physical and functional capacity 10,[22][23][24] . Furthermore, the classification through the IPAQ questionnaire did not distinguish patients in terms of pulmonary function, differently from what occurred when patients were categorized according to the 6MWD.…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, they show a reduction in protein degradation, production of lactic acid, resistance to insulin and resting heart rate 8 . Stretching and aerobic exercises can also contribute to the improvement of posture and quality of life 9,10 . The assessment of the capacity to exercise in patients with CF is usually performed through the six-minute walk test (6MWT) or maximal effort test 11 .…”
Section: Introductionmentioning
confidence: 99%